Religinė ir pilietinė tapatybė LDK Apšvietos pamoksluose - Mačiulytė, Kristina (Literatūra, 2015)
The second half of the 18th century in the Republic of the Two Nations witnessed an active shaping of identity of a person that was determined to a large extent by the European cultural, social trends and dramatic political situation of the State.An important factor shaping the identity of the Enlightenment person was the system of education, aimed to nurture Christian and civic values, awareness of contemporary problems and thorough preparation of a person to fulfil the commitments of his class. As the secular trends in Europe were increasingly growing, the Enlightenment in the Republic of the Two Nations manifested itself as an epoch strengthening the traditional Christian values. Without questioning the fundamental truths of the revealed religion, the efforts were made to rationalize certain church practices and to encourage more conscious confession of faith.Sermons of the second half of the 18th century actively considered the issue of status and rights of the lower classes (in the first place – of the villeinage peasants) and the reasoning for recognising them as “citizens” (namely the economic reasoning, relating to the importance of the labour and patriotic reasoning during the T. Kościuszko revolt).After the third division of the Republic, the issue of civic identity was complicated for all classes, irrespective of their position in the society. This tension was particularly emphasized in the addresses made for this occasion.